2013
DOI: 10.3409/fb61_3-4.271
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication Expression and Localization of Growth Hormone Receptor in the Oviduct of the Laying Hen (Gallus domesticus)

Abstract: The purpose of the present study was to examine growth hormone receptor (GHR) gene expression by real-time PCR and demonstrate immunocytochemically the localization of GHR in four chicken oviductal parts, i.e. infundibulum, magnum, isthmus and shell gland. Experiments were carried out on Hy-Line laying hens decapitated 2 h after oviposition. GHR mRNA was expressed in all examined oviductal segments with a significantly lower level in the infundibulum in comparison to other parts of the oviduct. Specific GHR im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…A stronger action of GH has been observed in the mucosa than in the stroma suggesting that the mucosa, in which proliferation is crucial for oviduct growth during maturation (Yu and Marquardt 1973), is mostly susceptible to GH. This justifies the previous suggestion of Hrabia et al (2013) that GH plays a regulatory role in the activity of the oviduct mucosa, since GH receptors in oviductal wall are localized predominantly in this tissue.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A stronger action of GH has been observed in the mucosa than in the stroma suggesting that the mucosa, in which proliferation is crucial for oviduct growth during maturation (Yu and Marquardt 1973), is mostly susceptible to GH. This justifies the previous suggestion of Hrabia et al (2013) that GH plays a regulatory role in the activity of the oviduct mucosa, since GH receptors in oviductal wall are localized predominantly in this tissue.…”
Section: Discussionsupporting
confidence: 91%
“…Oestrogens are the key steroids controlling oviductal growth and activity, via the regulation of cell proliferation and differentiation, and the synthesis of egg proteins (Dougherty and Sanders 2005). Ni et al (2007) have found the growth hormone (GH) receptor in the shell gland of the chicken oviduct and, recently, Hrabia et al (2013) have demonstrated the differential mRNA expression and protein localization of GH receptors in the infundibulum, magnum, isthmus and shell gland of laying hens and in the vagina (unpublished data); these findings suggest that chicken oviduct is also a GH-responsive organ. Moreover, hens injected with exogenous GH show increased eggshell quality of the eggs laid near the end of the laying period (Donoghue et al 1990).…”
Section: Introductionmentioning
confidence: 97%
“…Group Apoptosis Proliferation gland, but Hrabia et al (2013) later demonstrated differential mRNA expression of GHR in the infundibulum, magnum, isthmus and shell gland of laying hens. Recently GHR mRNA was also found in the vagina .…”
Section: Age [Weeks]mentioning
confidence: 98%
“…Most recent investigation showed that the chicken oviduct, like the ovary, is an extrapituitary site of GH production and a target organ for this hormone (Hrabia et al, 2013(Hrabia et al, , 2014bLuna et al, 2014). The avian oviduct is a unique organ divided morphologically and functionally into five parts.…”
Section: Participation Of Growth Hormone In Oviduct Functionmentioning
confidence: 99%
“…ough 88% of the albumen is water, this component of the egg contributes more than 60% to the total egg weight which is an essential quality of an egg [34]. Hrabia et al [35] have demonstrated differential mRNA expression and protein localization of GH receptors in the infundibulum, magnum, isthmus, and shell gland of laying hens.…”
Section: Introductionmentioning
confidence: 99%